2005
DOI: 10.1515/cllt.2005.1.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Dutch: From written MOGELIJK to spoken MOK

Abstract: In Dutch, high-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
(12 reference statements)
3
19
0
Order By: Relevance
“…7 For example, of recurrently lacks a vowel portion, and when it does have a vowel, it is recurrently central rather than back. It can also be seen that eigenlijk occurs in its highly reduced, monosyllabic form, as previously described by Ernestus (2000), Keune et al (2005) and Plug (2005). With reference to the two subtypes of repair, of the 27 instances with editing terms, 15 are error repairs and 12 are appropriateness repairs.…”
Section: Editing Termssupporting
confidence: 61%
“…7 For example, of recurrently lacks a vowel portion, and when it does have a vowel, it is recurrently central rather than back. It can also be seen that eigenlijk occurs in its highly reduced, monosyllabic form, as previously described by Ernestus (2000), Keune et al (2005) and Plug (2005). With reference to the two subtypes of repair, of the 27 instances with editing terms, 15 are error repairs and 12 are appropriateness repairs.…”
Section: Editing Termssupporting
confidence: 61%
“…We restricted ourselves to the recordings made in the Netherlands, since previous research suggests that speakers from the Netherlands and speakers from the Dutch speaking part of Belgium may show different reduction patterns (Keune, Ernestus, van Hout, & Baayen, 2005). We focused on ten words (listed in Table 2) that occur in all components and that are known to be prone to reduction in casual conversations (e.g., Ernestus, 2000).These ten words are semantically weak and therefore seldom accented, which explains why they are so often reduced.…”
Section: Methodsmentioning
confidence: 99%
“…These studies confirm the general differences observed between male and female speech: women tend to use standard and prestigious forms more often than men (e.g., Labov, 1972), and they also tend to take the lead in language change (e.g., Chambers 1995;Labov, 2001). For instance, women delete glides (Phillips, 1994) and word-final /t/s and /d/s (Guy, 1991) less often than men in American English, and they less often reduce the suffix lijk /lək/, for instance to [k], in Dutch (Keune, Ernestus, Van Hout, Baayen, 2005). In contrast, women more often use reduced pronunciation variants that are the norm or have prestige and that may be used in more formal speech as well (and are therefore of a very different nature than the reduced variants attested only in spontaneous conversations).…”
Section: Differences Among Speakersmentioning
confidence: 99%